Rituximab: 13 open questions after 20 years of clinical use. (February 2017) - Pavanello, Francesca; Zucca, Emanuele; Ghielmini, Michele
Highlights: Rituximab improved the prognosis of all B-cell derived lymphoproliferative diseases, but despite 20 years of intensive use, it remains a drug with a number of still obscure characteristics and unanswered questions. In this review we address all these questions and analyze the literature addressing these aspects. Abstract: Rituximab improved the prognosis of all B-cell derived lymphoproliferative diseases, but despite 20 years of intensive use, it remains a drug with a number of still obscure characteristics and unanswered questions. These include the mechanism of action and of resistance, the optimal schedule, the interaction with chemotherapy, as well as predictive factors for response rate and duration. Despite being very well tolerated, the question of its long term side effects and the risks of the administration near to a pregnancy have only recently been addressed. Also the indications are still not all clear: rituximab induces remissions as a single agent and improves the effect of chemotherapy, but its use as maintenance or as a substitute for watch and wait is still debated. Also, it is still unclear if its efficacy derives at least partly by reducing the risk of histological transformation in indolent NHL and reducing the risk of CNS relapse in aggressive NHL. Finally, despite of 20 years of research, it is still unclear if rituximab can be efficiently substituted by biosimilars or new anti-CD20 antibodies. In this review we address all these questions and analyze the literature addressing these aspects.